Consumer well‐being and social responsibility of subsistence entrepreneurs in subsistence marketplace. Issue 1 (17th July 2020) - Azmat, Fara; Samaratunge, Ramanie; Ferdous, Ahmed
Abstract: Business malpractices, such as the sale of overpriced, underweight and adulterated foodstuffs and essential commodities, can pose serious threats to subsistence consumers' wellbeing, given they are more vulnerable than their affluent counterparts. Drawing on 40 interviews with subsistence entrepreneurs in Bangladesh and Sri Lanka, our findings provide insights into the interplay between religiosity and social responsibility of entrepreneurs. We further explore how socio‐economic conditions and local embeddedness—two important characteristics of individuals in subsistence marketplaces—moderate the relationship between religiosity and social responsibility of entrepreneurs, providing implications for consumer welfare at the macro‐level. Our research makes a distinctive contribution to three streams of literature relating to social responsibility, subsistence marketplaces, and consumer affairs, with specific policy implications. Abstract : Special issue on Subsistence Marketplaces